2019
DOI: 10.3892/etm.2019.8085
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine activates the PI3K/Akt pathway to inhibit hepatocyte apoptosis in rats with obstructive jaundice

Abstract: Obstructive jaundice (OJ) is a common disease in clinical surgery. The present study aimed to determine the effects of dexmedetomidine (Dex) on hepatocyte apoptosis in rats with OJ and also to explore the underlying mechanism. A total of 30 adult male Sprague Dawley rats were randomly divided into 3 groups: Sham group, bile duct ligation (BDL) group, and BDL+Dex group. The serum liver function index, expression levels of serum inflammatory factor interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…LY294002 pretreatment abolished the protective effects of DEX on LPS-induced inflammatory cell infiltration, oxidative stress, and apoptosis in the lungs. Similar to our results, a previous study found that DEX significantly reduced lung injury in rats with obstructive jaundice through activation of the PI3K/Akt/HIF-1α signaling pathway [ 35 ]. DEX decreased the expression of IL-6 and TNF-α in obstructive jaundice rats [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…LY294002 pretreatment abolished the protective effects of DEX on LPS-induced inflammatory cell infiltration, oxidative stress, and apoptosis in the lungs. Similar to our results, a previous study found that DEX significantly reduced lung injury in rats with obstructive jaundice through activation of the PI3K/Akt/HIF-1α signaling pathway [ 35 ]. DEX decreased the expression of IL-6 and TNF-α in obstructive jaundice rats [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Due to ET stimulation, Kupffer cells secrete a large number of active mediators, including cytokines such as IL-1β, IL-6, TNF-α, and reactive oxygen species (ROS). This also results in elevated hepatic function markers, eventually triggering the liver damage (Sato et al, 2016;Xie et al, 2019;Zou et al, 2020). In this study, serum IL-1β and IL-6 were increased in BDL rats and were reduced by RF.…”
Section: Discussionmentioning
confidence: 50%
“…The data showed that high doses of Dex at 10 µg/kg/h significantly decreased expression of the inflammation-related cytokines IL-1β, il-6 and TnF-α, W/d ratios and pathological changes in the Vili model rats. Several reports have demonstrated that dex reduces the apoptosis of various parenchymal and epithelial cells following inflammation or ischemia (30)(31)(32)(33). Similarly, H-Dex was found to significantly reduce alveolar epithelial cell apoptosis.…”
Section: Discussionmentioning
confidence: 86%